Can non-Persians speak? The sovereign's narration of "Iranian identity". (October 2019) - Soleimani, Kamal; Mohammadpour, Ahmad
Since the late 19th century, despite multi-cultural and multilingual composition of Iranian population, Persian nationalism has functioned as the ideology of the state. Persian intelligentsia have formulated a set of historical and cultural referents that enabled them to present the Persian language and identity as primordial and all-inclusive of all Iranians. By the advent of the modern nation-state, during Pahlavi dynasty, the non-Persian identities were brutally repressed in favor of the "One Country, One Nation, and One Language" policy. Through the adoption of such a policy and with the help of Persian intellectual and literati classes, the state was able to impose Persian identity as the singular "Iranian identity" and systematically marginalize and criminalize the non-Persian identities, treating them as "manufactured ethnic identities." Being declared as "manufactured, " non-Persian identities are consequently perceived as constant threats to the territorial integrity and ideological monologue of the sovereign. This paper, therefore, aims to critically reassess "Iranian identity" and its production of "internal colonized Other." It argues that through such an "internal othering" that Persian nationalism, backed by the combined force of a military and "privileged epistemology" has generated and sustained "the process of internal colonization."